Effect of differences in stocking density in round tarpaulin ponds on growth and survival of Osphronemus gourami - Yudhistyan Hanif Rahmawan; Riza Rahman Hakim; Ganjar Adhywirawan Sutarjo (IJOTA (Indonesian Journal of Tropical Aquatic), 2020)
One way to increase cultivation productivity is by increasing stocking. Gouramy is a freshwater commodity that has a fairly slow growth performance. This study aims to determine the growth performance of gouramy reared at different stocking densities. The 3 cm gourami are reared in a pond containing 35 liters of water. ponds P1 (30 heads), P2 (50 heads), P3 (100 heads), P4 (150 heads), P5 (200 heads) each was repeated 3 times. Growth rate (GR), specific growth rate (SGR), survival rate (SR), and feed conversion ratio (FCR) were measured and analyzed for variance (ANOVA) followed by LSD. The results showed that the fish reared in pond P1 showed the best GR, SGR, FCR, and SR (3.8 g, 3.99 %, 96 %, and 1.11 respectively). The lower the density, the better the growth performance but based on efficiency and productivity the best is at P2.